2011
DOI: 10.1128/iai.01389-10
|View full text |Cite
|
Sign up to set email alerts
|

Multigenic Control and Sex Bias in Host Susceptibility to Spore-Induced Pulmonary Anthrax in Mice

Abstract: Mechanisms underlying susceptibility to anthrax infection are unknown. Using a phylogenetically diverse panel of inbred mice and spores of Bacillus anthracis Ames, we investigated host susceptibility to pulmonary anthrax. Susceptibility profiles for survival time and organ pathogen load differed across strains, indicating distinct genetic controls. Tissue infection kinetics analysis showed greater systemic dissemination in susceptible DBA/2J (D) mice but a higher terminal bacterial load in resistant BALB/cJ (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
(92 reference statements)
0
10
1
Order By: Relevance
“…DBA/2 mice have been found to be susceptible to lung infections which include influenza (Trammell et al, 2012), Mycobacterium tuberculosis (Cardona et al, 2003), Pseudomonas aeruginosa (Gosselin et al, 1995), and Bacillus anthracis (Yadav et al, 2011). In models of hypersensitivity pneumonitis, C57Bl/ 6 mice are sensitive to lung disease while DBA/2 are resistant, and differential cytokine expression (chiefly IL-12) is shown to be the determining factor (Gudmundsson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…DBA/2 mice have been found to be susceptible to lung infections which include influenza (Trammell et al, 2012), Mycobacterium tuberculosis (Cardona et al, 2003), Pseudomonas aeruginosa (Gosselin et al, 1995), and Bacillus anthracis (Yadav et al, 2011). In models of hypersensitivity pneumonitis, C57Bl/ 6 mice are sensitive to lung disease while DBA/2 are resistant, and differential cytokine expression (chiefly IL-12) is shown to be the determining factor (Gudmundsson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Host genetic traits that are determined or influenced by gender have been previously identified in diverse murine models of infective diseases [33], [34], [35], [36]. For protozoan parasites such as Plasmodium chabaudi, sex-biased hormonal differences are an important factor influencing host susceptibility [37], [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that differential susceptibility to group A Steptococci is also controlled by a single host genetic locus [122]. In contrast, a study by Yadav and colleagues [121] and the present study revealed that susceptibility to the bacterial pathogens Yersina pestis and Bp, respectively, involve multiple host loci. In fact, the only clear similarity between these two studies was that two of the weaker QTLs involved in susceptibility to Yersinia overlap with the QTL on chromosome 5 that was identified in the current studies on Bp.…”
Section: Discussioncontrasting
confidence: 49%
“…These findings are not surprising in light of findings that genetic factors play a key role in susceptibility to a wide range of other infectious diseases. Published findings have identified host genetic factors that are critical for variable susceptibility to intracellular parasites [115], viruses [116][117][118][119][120], and both intracellular [74,100,121] and extracellular [122] bacterial pathogens. Moreover, recent genome-wide studies have established novel associations between common polymorphisms and susceptibility to several infectious diseases that are responsible for significant morbidity and/or mortality in humans [73,100,123,124].…”
Section: Introductionmentioning
confidence: 99%